Study on Temporal and Spatial Distribution of Biogenic Elements of Sediment in Baiyangdian Lake. Issue 1 (March 2021) - Zhen, Han; Xiaobo, Liu; Shiyan, Wang; Pengfei, Yu
Abstract: Baiyangdian Lake is the largest macrophyte-dominated shallow lake in North China and the most important ecological barrier area in the Xiong'an New Area. Since the 1980s, the surface water of Baiyangdian Lake has been in a state of eutrophication for a long time due to high nitrogen and phosphorus content. Under the background of the gradual implementation of the New Area Planning Outline, the load of nitrogen and phosphorus from exogenous sources into the lake has been gradually controlled, and the nitrogen and phosphorus enriched in the sediment has increasingly become the main factor affecting water quality. Therefore, this study focused on the vertical and lateral distribution differences of total organic carbon, total nitrogen and total phosphorus contents in Baiyangdian Lake sediments. Meanwhile, combined with sedimentary years, the enrichment characteristics of nitrogen and phosphorus in different ages and their consistency with the change of total organic carbon content were analyzed. The study can provide some scientific reference for controlling the accumulation of nitrogen and phosphorus in Baiyangdian sediment and scientifically and orderly dredging.